2019
DOI: 10.5114/pm.2019.84156
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the frequency of consumption of foodstuffs on the risk of overweight and obesity in a group of post-menopausal women

Abstract: Introduction A noticeable change during the post-menopausal period is a modification of nutritional behaviors. The aim was to study the frequency of consumption of specific foodstuffs by post-menopausal women. Additionally, the influence of nutritional behaviors on the risk of overweight and obesity among post-menopausal women was assessed. Material and methods The study was conducted among 103 post-menopausal women in Poland in January to July 2016. It was a nationally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Anyżewska et al, 40 in a sample of male Polish Army personnel, reported no association between chocolate, chocolate candies, and candy bars; non‐chocolate candies; biscuits and cakes; ice cream and pudding; and salty snacks with BMI or a fat mass index. In a population of post‐menopausal Polish women, Górna et al, 48 observed that the frequency of consumption of sweet or salty DSs, which ranged from less than twice per month to at least six times a day, was not associated with the development of overweight or obesity. Despite 95% of a study population of Canadian University students consuming DSs, Brunt et al 42 reported no relationship between sweet baked goods, salty snacks, candy, and BMI.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Anyżewska et al, 40 in a sample of male Polish Army personnel, reported no association between chocolate, chocolate candies, and candy bars; non‐chocolate candies; biscuits and cakes; ice cream and pudding; and salty snacks with BMI or a fat mass index. In a population of post‐menopausal Polish women, Górna et al, 48 observed that the frequency of consumption of sweet or salty DSs, which ranged from less than twice per month to at least six times a day, was not associated with the development of overweight or obesity. Despite 95% of a study population of Canadian University students consuming DSs, Brunt et al 42 reported no relationship between sweet baked goods, salty snacks, candy, and BMI.…”
Section: Resultsmentioning
confidence: 99%
“…Although two studies reported higher EIs derived from a measure of DS consumption in individuals living with obesity compared to those without, 18,41 in studies investigating the effects of DS intake, portion size, and frequency, on various aspects of weight status, the results varied considerably. Among adults nine cross‐sectional studies, 15,40,42,48–50,56,57,59 indicated there was no relationship between a measure of DS intake and weight status, whereas five studies 15,18,46,59,62 reported a positive relationship, and four studies 47,49,54,57 indicated an inverse association. However, among the latter studies, the result was not maintained when excluding individuals with extreme weight categories 49 and was deemed not to be clinically significant in another 54 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations